Redesign of the Traditional Market in Tarutung City Using A Neo-vernacular Architectural Approach - Suwantoro, Hajar; Hutasoit , Renol (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
Along with the development of the times, people's markets are starting to be eliminated by the existence of supermarkets, malls and other shopping centers which are considered clean, comfortable, well organized, and also safe. This is also felt by the people's markets in North Tapanuli Regency. As an area that is a center for trade in agricultural products, North Tapanuli Regency still does not have a people's market that meets market building standards, especially the people's market in Tarutung (Onan Tarutung). Human needs that continue to develop require the support of facilities that can accommodate human activities in it. The problems that exist are the lack of awareness of market cleanliness, discomfort, unsafe, not well-organized zoning, and also not accessible to persons with disabilities. The lack of progress in the standard of living of the people in Tarutung has resulted in the slums of the market area continuing to increase so that the existence of people's markets is increasingly inferior to modern shopping centers. Therefore, the rejuvenation and development of the area that will be carried out at Onan Tarutung is through a neo-vernacular architectural approach, not only through physical form but through socio-cultural relations with the environment. The application of neo-vernacular architecture also provides a new function for the development of Onan Tarutung, namely the existence of the 'alaman' concept where sellers can sell in the middle of a mass of buildings which can give a natural impression in accordance with the huta batak concept, as well as the existence of flexible spaces such as plazas that can be used as community for social activities in the form of religious, cultural, and other social events.